Mean precipitable water vapour and rainfall liability index for the Indian area and neighbourhood (MAUSAM, 1971)
Mean monthly perceptible water vapour at 19 radiosonde stations in India, based on data for all years for which upper air ascents are available upto 1965 and 15 radiorisonde stations in the neighbouring countries have been calculated. The seasonal variations of precipitable water vapour and the mean monthly rainfall over the country are discussed. It is seen that the diversity in the magnitude of rainfall is not reflected by the values of the prccipitable water. There may be enough precipitable water at a place but dynamic factors like ascending currents etc may not be generally present to cause rain. As a rough indicator of the liability for rainfall at a place, the ratio of the mean monthly rainfall and the monthly mean precipitable water have been worked out for all the stations. Isopleths of this ratio-Rainfall Liability Index (RLI)-have been drawn for various months. It is felt that the maps of RLI over the country could be more meaningful and of greater practical utility for hydrological purposes than those of mean precipitable water alone.